ANALISIS PENGARUH LAPORAN KEUANGAN DAN FLEKSIBILITAS KAS TERHADAP PENGELUARAN INVESTASI DENGAN STRUKTUR KEPEMILIKAN SEBAGAI VARIABEL MODERASI (Studi Komparasi Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Sebelum Dan Pada Masa Covid-19) - Nina Kusumi Ningrum; Wisnu Mawardi (Jurnal Akuntansi dan Pajak, 2023)
The pandemic created a supply shock and negatively affected the global economy. In addition to tourism, another sector affected by the Covid-19 pandemic is manufacturing where there has been a decline in performance since the outbreak of the Covid-19 pandemic. This study aims to determine the effect of financial statements and cash flexibility on investment expenditures, as well as to determine the role of ownership structures in financial statements on investment expenditures in manufacturing companies in Indonesia. This type of research is descriptive qualitative research. The sample used in this study has certain criteria, namely manufacturing companies listed on the Indonesia Stock Exchange that have announced their financial statements in 2019 and 2020. In interpreting the results of the study, researchers analyzed the data with two analyses, namely Descriptive Statistics and Multiple Regression Analysis, namely Moderated Regression Analysis. From thecalculations, it can be seen that financial statements have a positive effect on investment expenditures, furthermore, it can be seen that cash flexibility has a positive effect on investment expenditures, and the results of calculating the moderation of the significance of the interaction of ownership structures with financial statements can be seen that the ownership structure does not moderate the influence of financial statements on investment expenditures. Financial statements have a positive effect on investment expenditures. Cash flexibility has a positive effect on investment expenditures. The ownership structure does not moderate the effect of financial statements on investment expenditures, with the type relating to crititerion and not interacting with predictors so that its role is more appropriate as an intervening. Further research suggestions use other coding variables such as inflation or SBI rate, as well as using companies with the same business family.